2010
DOI: 10.1590/s0100-204x2010000600006
|View full text |Cite
|
Sign up to set email alerts
|

Indicação de cultivares de feijoeiro-comum baseada na avaliação conjunta de diferentes épocas de semeadura

Abstract: Resumo -Os objetivos deste trabalho foram verificar a existência de interação entre genótipos de feijoeiro-comum e épocas de semeadura, avaliar a importância da interação complexa e verificar a necessidade de indicação de cultivares para cada época, em região de altitude intermediária nos estados do Paraná e Santa Catarina. Utilizaram-se avaliações de produtividade de grãos de 16 genótipos, em 12 ensaios realizados em duas épocas de semeadura. As análises de variância foram realizadas com decomposição da inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 6 publications
1
13
1
4
Order By: Relevance
“…On the other hand, the results of Pereira et al (2010) differed from those of this study and of Ramalho et al (1998), in that the G x L interaction was most important (5 %), followed by the G x Y (3 %) and G x S interaction (1.5 %). However, it is important to remember that this study was conducted in Parana and Santa Catarina, in the rainy and dry growing seasons, and that in these states the difference between growing seasons is much smaller, especially in relation to temperature and water supply during the growing period.…”
Section: Resultscontrasting
confidence: 95%
See 2 more Smart Citations
“…On the other hand, the results of Pereira et al (2010) differed from those of this study and of Ramalho et al (1998), in that the G x L interaction was most important (5 %), followed by the G x Y (3 %) and G x S interaction (1.5 %). However, it is important to remember that this study was conducted in Parana and Santa Catarina, in the rainy and dry growing seasons, and that in these states the difference between growing seasons is much smaller, especially in relation to temperature and water supply during the growing period.…”
Section: Resultscontrasting
confidence: 95%
“…However, the interaction involving the most important source of genotype variation was G x LY (7.2 %), which was approximately four times higher than G x S, indicating that genotype assessments in multiple locations/ years are more important than evaluations in the two growing seasons (Table 2). In a study on the rainy and dry growing seasons in the states of Parana and Santa Catarina, Pereira et al (2010) found a little relevant G x S interaction, accounting for only 0.9 % of the total variation, while LY x G interaction was responsible for 5.9 %.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The effect of the GE interaction on common bean grain yield is pronounced and has been previously described (Carbonell et al, 2004;Melo et al, 2007;Pereira et al, 2009Pereira et al, , 2010Pereira et al, , 2012Torga et al, 2013). Therefore, it is important to perform tests in representative cultivation environments in order to determine the effect of the GE interaction on estimates of genetic parameters, both in the process of breeding segregating populations and when selecting superior lines.…”
Section: Introductionmentioning
confidence: 99%
“…Genotype by environment interaction has been frequently reported in common beans in association with the trait of grain yield (Ramalho et al, 1998;Carbonell et al, 2004;Oliveira et al, 2006;Melo et al, 2007;Pereira et al, 2009Pereira et al, , 2010Torga et al, 2013), although it has been less explored for other traits, such as crude fiber content. There are some research results, such as those by Londero et al (2006) and Silva et al (2013) that provide evidence that fiber content in common beans is influenced by the environment.…”
Section: Introductionmentioning
confidence: 99%